European Trade Union Distance Education: Potential and problems - Walker, Steve; Creanor, Linda (Proceedings of the International Conference on Networked Learning, 2000)
The growth of transnational corporations, and in Europe the development of a social dimension to the European Union have created greater needs for trade unions to collaborate at European and international levels. Education is a central activity of trade unions as preparation for action in the social and economic fields and the recent and rapid spread of the Internet has created an obvious opportunity to explore the role of computer mediated distance learning. The European Trade Union Distance Education project (EIUDE) is one example of a collaborative approach to networked learning, in the context of a particular community of practice.